On The Verge of a New Fusion: Theatre Space – Digital Space. - DIACONIȚA, Alexandra (Theatrical Colloquia, 2022)
We live in an era more and more attached and inclined towards a technological system which makes inevitable the fact that this system is becoming a part of the performing arts, characterized lately by impressive visual dimensions. The new concept of the 21 century, digital scene, represents just one step into a completely unknown world and at the same time, a completely vibrant world, in which we recognize the availability of the visual capacity. Through this text, we aim to define digital space, how far is it from the theatrical forms, if it can approach them in some way and how spatiality is being perceived. We investigate the possibility of the theatre to have its own leverage on this path, so we can decide if the digital transfer could determine theatre to repress its survival instinct and, in the end, to be silenced. At the same time, we aim to discover versions of digital theatre or theatrical versions of the digital world. We also speak about how theatre „speaks” or „shuts up” on digital platforms; how much theatre has transformed lately its mechanisms and if we could perceive the possibility of an ascending, so we can affirm that the theatre has become or it’s about to become a more accessible and visible art, almost being worthy of a cinema film notoriety. Silence, a rare condition of our century, can become theatre’s more characteristic and fatalist mood, a theatre that is very connected to the physical can risk its place by being out of its comfort zone and pushed into an unfinished world. If the theatrical forms have the capacity to survive in this transformational context, we could actually talk about an evolution of these forms towards ones that can determine theatre reform itself. In regards to this, starting from this point where theatre transforms its language, we can make an imaginative travel, invoking a possible future for a silenced theatre that can be silenced also by a new artistic structure, placed somewhere between theatre and film – digital theatre or online theatre.